A new genus and two new species of sea stars (Family Asterinidae) from Indonesian marine lakes, with notes on habitat and feeding ecology - Setiadi, Anargha (Zootaxa, 2019)
A new genus of asterinid asteroid, Limnasterias gen. nov. and two new species, Limnasterias oinops sp. nov. and L. estradivariae sp. nov. are described from two East Kalimantan marine lakes, Indonesia. Limnasterias is differentiated from other asterinid genera by a combination of features: high aspect body with thick tissue covering; extensive papulate area; numerous single papulae in up to five rows at ray sides; boot-shaped inferomarginal plates; appressed superactinal plates and absence of superambulacral plates. The ecology and conservation of these species and their unique habitat are discussed.